Recognition, Vulnerability and Trust. Issue 1 (1st January 2021) - Petherbridge, Danielle
ABSTRACT: This paper examines the question of whether recognition relations are based on trust. Theorists of recognition have acknowledged the ways in which recognition relations make us vulnerable to others but have largely neglected the underlying 'webs of trust' in which such relations are embedded. In this paper, I consider the ways in which the theories of recognition developed by Jürgen Habermas and Axel Honneth, not only point to our mutual vulnerability but also implicitly rely upon mutual relations of trust. The paper first offers a novel examination of the relation between recognition, vulnerability and trust in Habermas' account of communicative action with the aim of arguing that such a consideration helps to elucidate important features of recognition. My claim is that a consideration of the dynamics of recognition and vulnerability in language-use, leads to an acknowledgment of the forms of trust that not only underpin communicative action, but recognition more generally. I conclude by considering the elements that are underplayed in Habermas' account by turning to an examination of Axel Honneth's alternative affective theory of recognition, specifically considering the interrelation between vulnerability and recognition. In doing so, I also turn to a consideration of the kind of trust that must be assumed in Honneth's account of mutual recognition and point to a recognitive notion of trust.